All Days 2014
DOI: 10.2523/iptc-17422-ms
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Flow Meters Trial Testing in High GOR/GVF Environment

Abstract: Multiphase flow metering (MPFM) technology is gaining popularity and becoming the main well rate testing mechanism in some regions of the world. Yet, their application in measuring the flow rates of high gas-oil-ratio (GOR) and/or high gas volume fraction (GVF) wells has always been a challenge. A remote field located in the Southeastern part of Saudi Arabia commenced its production in the late 90's from a thin oil column lying between a large gas-cap and a water aquifer. Although, 84% of the thin-oil-column p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, the challenge associated with MPFMs is the accuracy of the reading for fluids with a high gas–oil ratio (GOR) or high gas volume fraction (GVF). The MPFM accuracy decreases as the GVF increases more than 85% . In addition, Ganat et al compared MPFM measurements vs testing separators, and they found that MPFMs were unreliable in a high water-cut environment with an error that can reach 50% at a water cut of 61% .…”
Section: Introductionmentioning
confidence: 99%
“…However, the challenge associated with MPFMs is the accuracy of the reading for fluids with a high gas–oil ratio (GOR) or high gas volume fraction (GVF). The MPFM accuracy decreases as the GVF increases more than 85% . In addition, Ganat et al compared MPFM measurements vs testing separators, and they found that MPFMs were unreliable in a high water-cut environment with an error that can reach 50% at a water cut of 61% .…”
Section: Introductionmentioning
confidence: 99%